Kinetics of extracting valuable components from Ti-bearing blast furnace slag by acidolysis with sulphuric acid - Wang, Yan; Gao, Xin; He, Siqi; Guo, Jun (Frontiers in Chemistry, 2024)
Ti-bearing blast furnace slag is a kind of solid waste produced by Pangang Group Company through the blast furnace smelting method. A variety of valuable components can be extracted from the Ti-bearing blast furnace slag after acidolysis with concentrated sulphuric acid. In order to study the kinetics of acidolysis, this paper investigated the effects of the acidolysis temperature, acid-slag ratio and raw material particle size on the overall extraction rate of Ti 4+ , Mg 2+ and Al 3+ components at different reaction times, and simulated the acidolysis process by using the unreacted shrinking core model. The results showed that the acidolysis process was controlled by internal diffusion with an apparent activation energy of 19.05 kJ•mol -1 and the semi-empirical kinetic equation of the acidolysis process was obtained.